SOSIALISASI BUDIDAYA TANAMAN PINANG BETARA (ARECA CATECHU L ) (PENGOLAHAN LAHAN, PEMELIHARAAN DAN PANEN) DI DESA OMBOLATA KECAMATAN AFULU KABUPATEN NIAS UTARA - Karunia Gea; Nonozisokhi Gea (Universitas Nias Raya, 2023)
The purpose of this service activity is to provide socialization to the community on how to manage betel nut plants through land management, maintenance and post-harvest. The method used in this service is the lecture method in the form of outreach delivered through areca nut farmers in Ombolata Afulu Village, Afulu District. The results obtained in the service carried out were that through this socialization the community through socialization regarding the cultivation of betara betel plants, especially in the fields of land management, maintenance and harvesting, received a good response from all participants. This was evidenced by the large number of people who wanted to hear about the processes and cultivation of the betel nut plant, besides that the community also asked many questions that the public still did not know about the process of cultivating the betel nut in detail and comprehensively to the presenter. The conclusion from this community service activity is that the village community in cultivating areca plants is very enthusiastic about what other benefits can be obtained both for cultivation on the Nias Islands to help the community's economy, especially on the Nias islands.